2004
DOI: 10.1017/s0952836904005904
|View full text |Cite
|
Sign up to set email alerts
|

Nesting success of hawksbill turtles (Eretmochelys imbricata) on Cousine Island, Seychelles

Abstract: Nesting hawksbill turtles Eretmochelys imbricata were studied on Cousine Island, Seychelles from 1995 to 1999. Mean overall incubation time averaged 58.1 days. Clutch size did not influence incubation periods. Following hatching, hatchlings took an average of 3.8 days to leave the nest. Mean hatchling emergence time was 60.4 days. Hatching success averaged 64.3% for the four seasons. During 1996-97 there were heavy, unexplained egg losses due to crab predation. Excluding that season, average hatching success w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 7 publications
0
23
1
2
Order By: Relevance
“…For example, hawksbill turtle (Eretmochelys imbricata) nest predation by ghost crabs (Ocypode cordimana) on Cousine Island (Seychelles) was relatively low (aprox. 17%) when there was an absence of bigger predators (Hitchins et al, 2004) compared to the nest predation found in the present study. For green turtle (Chelonia mydas) nests, average predation by ghost crabs (Ocypode ceratophtalmus and Ocypode kuhlii) in the Malaysian island of Mak Kepit was also very low (aprox.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…For example, hawksbill turtle (Eretmochelys imbricata) nest predation by ghost crabs (Ocypode cordimana) on Cousine Island (Seychelles) was relatively low (aprox. 17%) when there was an absence of bigger predators (Hitchins et al, 2004) compared to the nest predation found in the present study. For green turtle (Chelonia mydas) nests, average predation by ghost crabs (Ocypode ceratophtalmus and Ocypode kuhlii) in the Malaysian island of Mak Kepit was also very low (aprox.…”
Section: Discussioncontrasting
confidence: 53%
“…Therefore, for ghost crabs and other predators, turtle eggs are a temporal resource that they efficiently use, but alternative food sources are required for the rest of the year. Several studies show that when there is an absence in turtle eggs, ghost crabs may feed on many other species (Chartosia et al, 2010;Hitchins et al, 2004), which proves that their survival does not exclusively depend on sea turtle conservation. The ghost crab is an opportunistic feeder (Strachan et al, 1999;Trott, 1999) that feeds on particulate organic matter found in between the grains of sand, dead fish and other dead animals on the beach, as well as lizards, other crabs, insects, birds and small mammals (Hitchins et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Also, various scientists were encouraged to visit the island to undertake various studies of key species and processes, such as reptiles (Bourquin and Hitchins 1998), Seychelles giant millipede biology (Lawrence and Samways 2003), assessment of the invertebrates of the leaf litter and logs (Kelly and Samways 2003), spider assessments (Saaristo 1999), colonization by dragonflies (Samways 1998(Samways , 2003a, Seychelles warbler (Komdeur 1994(Komdeur , 1995 and Seychelles magpie robin biology (Komdeur 1996;LeMaitre 2002), turtle biometrics and nesting biology (Hitchins et al 2003a(Hitchins et al , b, 2004a(Hitchins et al , b, 2006, and marine assessments (Samways 2003a, b;Samways and Hatton 2001).…”
Section: The Early Phase Of Restorationmentioning
confidence: 99%
“…Nest management is a valuable practice adopted in many nesting sites, as it may reduce risks of predation, erosion and/or human threat (Wyneken et al 1988, Eckert and Eckert 1990, Marcovaldi and Laurent 1996, Hitchins et al 2004. Nests at risk due to erosion and flooding by tides are often transported to hatcheries or to safer places on the beach mainly on the beach berm, where the sand is covered by beach vegetation of varying density.…”
Section: Introductionmentioning
confidence: 99%